SUMOylation involved in malignant progression of multiple tumors and SENP5 may improve the chemotherapy sensitivity of hypoxic tumors - Zhang, Chunyan; Han, Bing; Li, Yanxia; Wang, Yuxiang; Liu, Min; Jiang, Zhongmin; Wu, Wenhan; Liu, Xiaozhi; Liu, Yafei; Liu, Mingyong (Frontiers in Pharmacology, 2025)
IntroductionSmall ubiquitin-related modifier (SUMO), a ubiquitin-like modification protein, is implicated in the aggressive progression of various tumor types. However, a comprehensive understanding of its mechanisms and the identification of therapeutically viable targets remain challenging.MethodsWe analyzed the expression and clinical relevance of SUMO pathway components using public cancer databases (e.g., TCGA). The functional role of SUMOylation was investigated under varying oxygen conditions in vitro. The core SUMOylation enzyme UBC9 was inhibited pharmacologically with Spectinomycin B1 UBC9. The tumor-specific role of SENP5 was validated through genetic knockdown and overexpression in a panel of tumor cell lines and tumor-derived organoids. To assess the potential for off-tumor toxicity, the effects of UBC9 inhibition and SENP5 targeting were further evaluated in organoids derived from fetal mouse liver and kidney.ResultsSUMO signaling was significantly activated in multiple tumors and correlated with poor prognosis. We demonstrated that oxygen levels modulate chemotherapy sensitivity via regulation of SUMOylation. While UBC9 inhibition broadly suppressed tumor progression through global deSUMOylation, it also induced toxicity in normal organoids. In contrast, SENP5 was specifically overexpressed in tumors and mediated selective removal of SUMO2/3 modifications, affecting a narrower range of substrates.DiscussionOur findings indicate that inhibition of the SUMOylation pathway is a promising therapeutic strategy. The broader implication of our study is that the precision and safety of this approach are contingent upon targeting specific components such as SENP5, which offers a superior therapeutic window by avoiding the adverse effects associated with global SUMOylation inhibition.